2015
DOI: 10.1371/journal.pone.0139216
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Risk-Standardized Mortality of Stroke among Hospitals in Japan

Abstract: Despite recent advances in care, stroke remains a life-threatening disease. Little is known about current hospital mortality with stroke and how it varies by hospital in a national clinical setting in Japan. Using the Diagnosis Procedure Combination database (a national inpatient database in Japan), we identified patients aged ≥20 years who were admitted to the hospital with a primary diagnosis of stroke within 3 days of stroke onset from April 2012 to March 2013. We constructed a multivariable logistic regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
1
9
0
1
Order By: Relevance
“…[33][34][35][36] Other outcomes than mortality have also been investigated such as referral to and enrolment in a chronic disease management programme for cardiac rehabilitation which was less likely in patients in Ontario, Canada who lived 60 or more minutes from a cardiac rehabilitation site. 37 Therefore, it is important to distinguish healthcare usage from emergency treatment in the association of accessibility of healthcare facilities and outcomes.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…[33][34][35][36] Other outcomes than mortality have also been investigated such as referral to and enrolment in a chronic disease management programme for cardiac rehabilitation which was less likely in patients in Ontario, Canada who lived 60 or more minutes from a cardiac rehabilitation site. 37 Therefore, it is important to distinguish healthcare usage from emergency treatment in the association of accessibility of healthcare facilities and outcomes.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…Stroke mortality is known to be associated with patient and hospital related aspects. Studies showed that increased probability of in-hospital mortality is associated with increasing age [ 6 , 7 , 8 ] and significantly higher among women as compared to men [ 6 , 9 ].The hospital related factors include, availability of a stroke care unit and the patient’s residence related to the hospital [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, most stroke patients (75.8%) were aged older than 60. our ndings indicate that age represents an important independent factor of death so that overall, each additional year is associated with a 3% relative increase in in-hospital stroke mortality. Studies indicated an increased probability of inhospital stroke mortality is associated with increasing age (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%